2011
DOI: 10.1186/1745-6215-12-s1-a42
|View full text |Cite
|
Sign up to set email alerts
|

What is the value of collecting detailed costing data in clinical trials?

Abstract: Cost data for trial-based economic evaluation can be obtained through micro-costing (collecting resource use and unit cost data for each centre or patient), grosscosting (average costs based on top-line budgets) or provider tariffs (e.g. healthcare resource groups, HRGs). Most studies use a combination of approaches due to data availability, although there is little guidance on which is best. We report a systematic comparison of the three costing approaches in IVAN: a non-inferiority randomised controlled fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This could induce omitted-variable bias, if methodological differences were correlated with regression variables, or if cost estimates were biased systematically. For example, it has been observed that costing studies may over- or underestimate costs due to the costing approach used (i.e., gross costing vs. micro-costing [ 56 ]) or may underestimate costs due to the exclusion of relevant intervention cost categories [ 57 ]. In our analysis, we saw that excluding outliers changed the magnitude, although not the direction, of several regression coefficients, as shown in the results of Appendix Table C. All included studies were reported from the immunization provider perspective, and excluded caregiver/beneficiary time and transportation costs to receive vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This could induce omitted-variable bias, if methodological differences were correlated with regression variables, or if cost estimates were biased systematically. For example, it has been observed that costing studies may over- or underestimate costs due to the costing approach used (i.e., gross costing vs. micro-costing [ 56 ]) or may underestimate costs due to the exclusion of relevant intervention cost categories [ 57 ]. In our analysis, we saw that excluding outliers changed the magnitude, although not the direction, of several regression coefficients, as shown in the results of Appendix Table C. All included studies were reported from the immunization provider perspective, and excluded caregiver/beneficiary time and transportation costs to receive vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Given the difficulties associated with direct microcosting measurements, analysts are interested in finding easier methods of cost estimation that are still valid. [10] One such method is the use of modelling in place of direct costing. Gross-costing modelling approaches comprise a number of methods that charge at a more highly-aggregated level of service provision (e.g.…”
Section: Microcosting Vs Gross Costing Methodsmentioning
confidence: 99%
“…If the cost of an intervention is unknown, it can be estimated using a micro-costing or a gross-costing approach. 1,33,36,78,79 In a micro-costing approach (i.e. bottom-up approach), information on the types and quantities of resources consumed as well as their respective unit prices is collected for each intervention component separately.…”
Section: Intervention Costsmentioning
confidence: 99%
“…It allocates a total budget to specific services, such as physical therapists' visits, using specific allocation rules. 1,33,36,78,81,82 The average intervention cost per patient might, for example, be estimated by simply dividing the total intervention costs by the number of patients. Although gross-costing is a simple and fast approach, it lacks precision and its success depends on the type of routine data available.…”
Section: Intervention Costsmentioning
confidence: 99%